2012
DOI: 10.1253/circj.cj-12-0665
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Using Strain Echocardiography to Evaluate the Left Ventricle

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp valuation of left ventricular (LV) systolic function is a critical component of the practice of cardiology and a fundamental function of the echocardiographic examination. Although LV systolic function is commonly defined by ejection fraction (EF), there are numerous technical and hemodynamic limitations to EF. A qualitative "eyeball" estimate has high variability, and quantitative measurements are subject to endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 19 publications
(10 reference statements)
1
74
1
4
Order By: Relevance
“…This method relies only on two planes and is based on mathematical assumption. Furthermore, it does not yield the complexity of LV mechanics even when supported by 3D acquisition [6,[36][37][38]. In our study, no significant differences in traditional echocardiographic parameters of a systolic and diastolic function of LV were observed.…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…This method relies only on two planes and is based on mathematical assumption. Furthermore, it does not yield the complexity of LV mechanics even when supported by 3D acquisition [6,[36][37][38]. In our study, no significant differences in traditional echocardiographic parameters of a systolic and diastolic function of LV were observed.…”
contrasting
confidence: 56%
“…Several studies have reported complete recovery of LV systolic function in patients with TTC as analyzed by the LV ejection fraction (LVEF) during follow-up [1][2][3]. Two-dimensional speckle tracking echocardiography (2D STE) is a valuable tool to evaluate global and regional LV function and appears to be more precise and distinctive than traditional echocardiography for detecting subtle myocardial abnormalities [4][5][6]. Apical and basal LV rotation have been described as an important part of LV twist, which plays a key role in maintaining both systolic and diastolic function [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first clinical use was suggested as early as 2003 (86), and today, further standards for the analyses of left myocardial function are being proposed (65). The use of apical views for the evaluation of cardiac deformation seems to be clinically useful (87), and apical views result in the best reproducibility (88). Analyses of systolic regional deformations (Figure 8), the diastolic properties in CHD, estimations of LV filling and left atrial function (73) are further advantages of this technology.…”
Section: Novel Techniques and Screening For Ischemiamentioning
confidence: 99%